Preparation and Optimization of 10-Hydroxycamptothecin Nanocolloidal Particles Using Antisolvent Method Combined with High Pressure Homogenization. (24th May 2017) - Lian, Bolin; Li, Yong; Zhao, Xiuhua; Zu, Yuangang; Wang, Ying; Zhang, Yin; Li, Yuanyuan
Abstract : The aim of this study was to prepare 10-hydroxycamptothecin nanocolloidal particles (HCPTNPs) to increase the solubility of drugs, reduce the toxicity, improve the stability of the drug, and so forth. HCPTNPs was prepared by antisolvent precipitation (AP) method combined with high pressure homogenization (HPH), followed by lyophilization. The main parameters during antisolvent process including volume ratio of dimethyl sulfoxide (DMSO) and H2 O and dripping speed were optimized and their effects on mean particle size (MPS) and yield of HCPT primary particles were investigated. In the high pressure homogeneous procedure, types of surfactants, amount of surfactants, and homogenization pressure (HP) were optimized and their influences on MPS, zeta potential (ZP), and morphology were analyzed. The optimum conditions of HCPTNPs were as follows: 0.2 mg/mL HCPT aqueous suspension, 1% of ASS, 1000 bar of HP, and 20 passes. Finally, the HCPTNPs via lyophilization using glucose as lyoprotectant under optimum conditions had an MPS of 179.6 nm and a ZP of 28.79 ± 1.97 mV. The short-term stability of HCPTNPs indicated that the MPS changed in a small range.